PARP-1 activity is required for the reconsolidation and extinction of contextual fear memory. Issue 1 (December 2015) - Inaba, Hiroyoshi; Tsukagoshi, Akinori; Kida, Satoshi
Abstract Background Memory consolidation, reconsolidation, and extinction have been shown to require new gene expression. Poly ADP-ribosylation mediated by poly (ADP-ribose) polymerase-1 (PARP-1) is known to regulate transcription through histone modification. Recent studies have suggested that PARP-1 positively regulates the formation of long-term memory (LTM); however, the roles of PARP-1 in memory processes, especially processes after retrieval, remain unknown. Results Here, we show critical roles for PARP-1 in the consolidation, reconsolidation, and extinction of contextual fear memory in mice. We examined the effects of pharmacological inhibition of PARP-1 activity in the hippocampus or medial prefrontal cortex (mPFC) on these memory processes. Similarly with previous findings, a micro-infusion of the PARP-1 inhibitor 3-aminobenzamide or PJ34 into the dorsal hippocampus, but not mPFC, impaired LTM formation without affecting short-term memory (STM). Importantly, this pharmacological blockade of PARP-1 in the dorsal hippocampus, but not mPFC, also disrupted post-reactivation LTM without affecting post-reactivation STM. Conversely, micro-infusion of the PARP-1 inhibitors into the mPFC, but not dorsal hippocampus, blocked long-term extinction. Additionally, systemic administration of the PARP-1 inhibitor Tiq-A blocked c-fos induction in the hippocampus, which is observed when memory is consolidated or reconsolidated, and also blocked c-fos induction in the mPFC, which is observed when memory is extinguished. Conclusions Our observations showed that PARP-1 activation is required for the consolidation, reconsolidation, and extinction of contextual fear memory and suggested that PARP-1 contributes to the new gene expression necessary for these memory processes.